2020
DOI: 10.3389/fcell.2020.600304
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Lnc-CYP7A1-1 Rejuvenates Aged Human Mesenchymal Stem Cells to Improve Their Efficacy for Heart Repair Through SYNE1

Abstract: Background: Several long non-coding RNAs (lncRNAs) have been associated with cell senescence, termed senescence-associated lncRNAs (SAL-RNAs). However, the mechanisms involved for SAL-RNAs in aging are not fully elucidated. In the present study, we investigated the effects of SAL-RNAs on aged human bone marrow-derived mesenchymal stem cells (hBM-MSCs), and the possible means to counteract such effects to improve the regenerative capacity of aged hBM-MSCs. Methods: By comparing the lncRNAs expression of hBM-MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…MSC‐based therapy has been identified as a promising intervention for MI because of the unique properties of MSCs: easy isolation and expansion, multiple lineage potential, and lack of immunogenicity. Nonetheless, their beneficial effects are dramatically hampered by their cellular senescence 29–31 . Compared with YMSCs, AMSCs display decreased proliferative capacity and reduced paracrine effects, especially their angiogenic capacity which is the major mechanism underlying MSC‐based therapy for MI 28,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC‐based therapy has been identified as a promising intervention for MI because of the unique properties of MSCs: easy isolation and expansion, multiple lineage potential, and lack of immunogenicity. Nonetheless, their beneficial effects are dramatically hampered by their cellular senescence 29–31 . Compared with YMSCs, AMSCs display decreased proliferative capacity and reduced paracrine effects, especially their angiogenic capacity which is the major mechanism underlying MSC‐based therapy for MI 28,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, their beneficial effects are dramatically hampered by their cellular senescence. [29][30][31] Compared with YMSCs, AMSCs display decreased proliferative capacity and reduced paracrine effects, especially their angiogenic capacity which is the major mechanism underlying MSC-based therapy for MI. 28,32 More importantly, AMSCs exhibit a decreased survival capacity in ischemic heart tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dong et al discovered that long non-coding RNA (lnc), lnc-CYP7A1-1, stimulated senescence in human BM-MSCs, and its downregulation subsequently improved regenerative capacities and decreased cell senescence in vitro [116]. Consequently, transplantation of old human BM-MSCs with downregulated lnc-CYP7A1-1 improved cardiac function in mice after myocardial infarction.…”
Section: Therapeutic Implications Of Msc Senescence Targetingmentioning
confidence: 99%
“… 19 , 20 With the gradual deepening of the research on LncRNAs, many studies have reported that LncRNAs regulate gene expression at the epigenetic, transcriptional, and post‐transcriptional levels, and have a potential regulatory effect on the cell fate of mesenchymal stem cells and the occurrence and development of specific diseases. 19 , 21 , 22 In particular, studies have confirmed that LncRNAs affect the expression of specific genes by regulating the DNA methylation level in their promoter region. 23 , 24 , 25 However, the molecular mechanism of LncRNAs in regulating the osteogenic differentiation and bone regeneration of DOP‐ASCs is unclear.…”
Section: Introductionmentioning
confidence: 97%